The Bible Story : More Than Four Hundred Stories in Ten Volumes Covering the Entire Bible From Genesis to Revelation - Maxwell, Arthur S. (Paciffic Press Publishing Association, 1956)
Beautifully written by renowned children's author, Arthur S. Maxwell (aka Uncle Arthur), and illustrated on almost every page. These fine, hardcover books are the most comprehensive set of Bible stories for children that we have seen. This set has the quoted Bible texts taken from the New International Version (NIV). * Written especially for the elementary school ages, easy to read & understand. * 1200 color illustrations! 409 stories in 10 volumes! * Stories are true to the Bible. * Entire Bible is covered, beginning with stories from Genesis in volume 1 and ending with stories from Revelation in volume 10. Volume 1: The Book of Beginnings Volume 2: Mighty Men of Old Volume 3: Trials and Triumphs Volume 4: Heroes and Heroines Volume 5: Great Men of God Volume 6: Struggles and Victories Volume 7: Wonderful Jesus Volume 8: Prince of Princes Volume 9: King of Kings Volume 10: Onward to Glory These lovely Bible story books offer many features to enhance Bible study. * Each book is arranged in sections with the Bible texts given from which that section's stories are taken. * Book 1 contains four indexes covering the entire set: for locating stories about Bible Men & Women; Great Bible Teachings & Character Building Lessons; Books of the Bible; and a complete list of all 409 stories in the set. * The bindings are durable and you can easily wipe sticky fingerprints from the colorful mylar hardcovers. Published jointly by the Pacific Press Publishing Association and the Review and Herald Publishing Association. MSRP for a new set like this is 75.00. We are able to offer this set at an excellent price!